Congenital High Airway Obstruction Syndrome (CHAOS): No Intervention, No Survival—A Case Report and Literature Review - Ammar Ashraf; Ahmed Mohamed Abdelrahman; Ahmed Senna; Fatimah Alsaad (Case Reports in Radiology)
Congenital high airway obstruction syndrome (CHAOS) is complete or partial obstruction of the fetal upper airway. CHAOS is a rare and fatal condition if no perinatal intervention is done. Antenatal sonographic imaging has typical findings that can help in an early diagnosis, which is important in deciding elective termination of the pregnancy or successful planning of appropriate perinatal management.